Pengaruh Pendapatan Daerah Terhadap Pertumbuhan Ekonomi di Wilayah Surabaya Raya (Surabaya, Sidoarjo, Gresik) - Novita Dwi Indriyani; Eko Wahyudi (Yos Soedarso Economic Journal (YEJ), 2021)
The purpose of this study was to determine the effect of Regional Original Income (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK) and Revenue Sharing Fund (DBH) on economic growth in the Greater Surabaya area of ​​East Java Province. This research was conducted in the Greater Surabaya area, East Java Province using the saturated sampling method in determining the sample with the population and the sample being the City of Surabaya, Sidoarjo Regency, Gresik Regency in 2015 - 2019. Data collection was carried out through non-participant observation techniques. Data analysis was performed using descriptive analysis and multiple linear regression. Based on the results of the study, it shows that Regional Original Income (PAD) and Special Allocation Funds (DAK) have a positive effect on economic growth in the Greater Surabaya area, East Java Province. Meanwhile, the General Allocation Fund (DAU) and Revenue Sharing Fund (DBH) have a negative effect on economic growth in the Greater Surabaya area. Keywords : Economic Growth; Regional Income; Greater Surabaya.